DIGO: An Open Data Architecture for e-Government - Machado, A. L.; Parente de Oliveira, Jose Maria (2011 IEEE 15th International Enterprise Distributed Object Computing Conference Workshops, 2011)
Currently most governing bodies publish their data on the World Wide Web (WWW). These data are available on e-Government Web Portals in unstructured formats using current Web languages, making them difficult to reuse and to generate new information. In this context, access to relevant, accurate public information, and possible reuse by other applications become increasingly complex. Open Government Data (OGD) means the publication of data in open raw formats (open data). There are tools to put open data on the WWW. However, this tools doesn't work with an architecture covering all aspects of data reuse. The aim of this paper is to show an architecture called Delivering Information of Government (DIGO) to allow access to primary data by machines in open data so that citizens interested in doing so can combine them (linked open data) and produce new information and mashup applications, consequently, enabling OGD and data fusion on the Linking Open Data (LOD) cloud.